Linking supply chain disruption orientation to supply chain resilience and market performance with the stimulus-organism-response model - Aaron Rae Stephens; Minhyo Kang; Charles Arthur Robb (Journal of Risk and Financial Management, 2022)
Since 2020, supply chain disruptions have emerged as an ever-present challenge. This research provides a glimpse into the organizational structures that develop supply chain resilience and market performance amid continuous supply chain disruptions. Utilizing psychosomatic variables and empirical modeling, a model was constructed through a review of extant literature and tested with PLS-SEM analysis. Uniquely, this research model is framed with the stimulus-organism-response model; thus, placing a firm within the context of a tumultuous environment where stimuli elicit responses from an organization that behaves as an organism. Results demonstrate that organizational culture plays a critical role in developing supply chain resilience amid supply chain dynamism. Market performance was also developed but only through supply chain resilience; supply chain disruption orientation alone did not improve market performance. Mediation effects highlight the importance of supply chain disruption orientation, a strategic orientation that cements an organization's ability to develop supply chain resilience.
Keywords: 650; market performance; stimulus-organism-response model; supply chain disruption orientation; supply chain dynamism; supply chain resilience